The global burden of chronic kidney disease attributable to high sodium intake: a comprehensive analysis of trends from 1990 to 2021 and burden prediction to 2040 - Lu, Yawen; Wang, Lei; Ma, Jianfeng; Hu, Yang; Zheng, Rumeng; Liu, Liping; Lin, Kaili; Zhang, Kun; Wang, Yongfeng; Li, Sheng; Li, Hengping (Frontiers in Nephrology, 2025)
BackgroundChronic kidney disease (CKD) is a progressive condition affecting over 10% of the global population, with high sodium intake identified as a critical modifiable risk factor. This study investigated the global burden of CKD due to excessive sodium intake in 204 countries and territories from 1990 to 2021 and made the first future projections to 2040, addressing gaps in longitudinal analysis of sodium-related CKD trends and demographic differences.MethodsData from the Global Burden of Disease (GBD) 2021 database were analyzed to quantify CKD-related deaths and disability-adjusted life years (DALYs) linked to high sodium intake. Age-standardized mortality rates (ASMR) and DALY rates (ASDR), alongside the sociodemographic index (SDI), were used to assess regional and demographic variations. Statistical analyses in R included joinpoint regression to identify temporal inflection points and age-period-cohort (APC) modeling to disentangle age, period, and birth cohort effects. Future projections show that from 2021 to 2040, the global ASMR trend is stabilizing and ASDR is on the rise. Moreover, male ASMR and ASDR have been consistently higher than female ASMR. This gender difference is expected to continue for a long time, with men continuing to bear a greater burden of chronic kidney disease than women.ResultsBetween 1990 and 2021, global CKD deaths attributed to high sodium intake surged 1.68-fold (26,072 to 69,954), while DALYs increased by 135% (741,197 to 1,705,325). ASMR and ASDR rose markedly in high-income regions (20.73% and 6.77%, respectively), with Latin America and the Caribbean reporting the highest burdens (ASMR: 1.49/100,000; ASDR: 33.21/100,000). Men exhibited consistently higher burdens than women, peaking in the 65–79 age group. Low SDI regions showed declining trends, contrasting with widening inequalities in medium SDI areas.ConclusionThe global CKD burden attributable to high sodium intake has escalated dramatically over three decades, driven by aging populations, dietary shifts, and regional disparities. Urgent, targeted interventions—such as sodium reduction policies, gender-specific health strategies, and enhanced healthcare access—are critical to curbing this trend, particularly in high-risk demographics and high-income regions.